Negligible risk of surface transmission of SARS-CoV-2 in public transportation - Pilipenco, Alina; Forinová, Michala; Mašková, Hana; Hönig, Václav; Palus, Martin; Lynn, Nicholas Scott; Víšová, Ivana; Vrabcová, Markéta; Houska, Milan; Anthi, Judita; Spasovová, Monika; Mustacová, Johana; et al. (Journal of travel medicine, 2023)
BACKGROUND: Exposure to pathogens in public transport systems is a common means of spreading infection, mainly by inhaling aerosol or droplets from infected individuals. Such particles also contaminate surfaces, creating a potential surface-transmission pathway. METHODS: A fast acoustic biosensor with an antifouling nano-coating was introduced to detect severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) on exposed surfaces in the Prague Public Transport System. Samples were measured directly without pre-treatment. Results with the sensor gave excellent agreement with parallel quantitative reverse-transcription polymerase chain reaction (qRT-PCR) measurements on 482 surface samples taken from actively used trams, buses, metro trains and platforms between 7 and 9 April 2021, in the middle of the lineage Alpha SARS-CoV-2 epidemic wave when 1 in 240 people were COVID-19 positive in Prague. RESULTS: Only ten of the 482 surface swabs produced positive results and none of them contained virus particles capable of replication, indicating that positive samples contained inactive virus particles and/or fragments. Measurements of the rate of decay of SARS-CoV-2 on frequently touched surface materials showed that the virus did not remain viable longer than 1-4 h. The rate of inactivation was the fastest on rubber handrails in metro escalators and the slowest on hard-plastic seats, window glasses and stainless-steel grab rails. As a result of this study, Prague Public Transport Systems revised their cleaning protocols and the lengths of parking times during the pandemic. CONCLUSIONS: Our findings suggest that surface transmission played no or negligible role in spreading SARS-CoV-2 in Prague. The results also demonstrate the potential of the new biosensor to serve as a complementary screening tool in epidemic monitoring and prognosis.
Keywords: respirační aerosoly a kapénky; doprava; public transportation; pandemie; COVID-19; Pandemics; surface contamination; Humans; Respiratory Aerosols and Droplets; qRT-PCR; SARS-CoV-2; quartz crystal microbalance; lidé; Transportation; antifouling biosensor; Prague